Implementation of the Policy for Capacity Building of Village Apparatus in Merangin Regency, Jambi - Pahrudin HM; Burlian Senjaya (The Journal of Society and Media, 2021)
This study is intended to analyze the implementation of policies carried out by the Merangin Regency Government of Jambi Province in order to increase the capacity of village apparatus. This study used Weimer and Vining's policy implementation, which consists of policy logic, policy environment and implementor capability. This research was conducted using a qualitative approach with a type of case study. Data collection was carried out by interviewing 11 respondents and reviewing data related to the research topic. After collected, the data were analyzed by data reduction, data presentation, and drawing conclusions. Based on this research, it is known that in terms of policy logic, the Merangin Regency Government really understands the significance of the existence of village officials in managing existing resources, so it does Workshop on the Implementation of SISKEUDES and Provision of Village Technical Capacity Development (P2KTD) was held. The policy environment also supports the implementation of this policy through commitments conveyed by the Head of Regency, Head of the Merangin Regency Village Community Development Agency (PMD) and Heads of Sub-Districts. The ability of implementors consisting of village officials is still very limited in applying training materials in accordance with the potential context of their respective villages.